STUDI TENTANG KALIGRAFI ARAB DI MASJID RAYA ALMUNAWWARAH KAPENCONG LUBUK GAMBIR BAYANG PESISIR SELATAN - AJI WASKITO, Drs. Efrizal, M.Pd., Drs. Syafei, M. Ag. (Universitas Negeri Padang, 2016)
This study aims to: Describe 1) types of Arabic calligraphy 2) formsof Arabic calligraphy 3) the meaning of Arabic calligraphy inmosque Almunawwarah highway. The research method usingqualitative research with descriptive approach. The results showedthat in the grand mosque with Arabic calligraphy Almunawwarahthere are several types of Arabic calligraphy that khat Koufi, Tsuluskhat, khat Diwani, and khat naskhi. Forms of Arabic calligraphyAlmunawwarah grand mosque is a circular shape, a semi-circular,rectangular, and octagonal. The meaning of Arabic calligraphyAlmunawwarah grand mosque is the meaning of visual, textual andcontextual.Keywords: Type, Form, Meaning of Arabic Calligraphy